Impact of extreme pre-monsoon drought on xylogenesis and intra-annual radial increments of two tree species in a tropical montane evergreen broad-leaved forest, southwest China - Liu, Ya Nan; Fan, Ze Xin; Lin, You Xing; Kaewmano, Arisa; Wei, Xiao Lian; Fu, Pei Li; Grießinger, Jussi; Bräuning, Achim (Tree Physiology, 2024)
Tropical montane evergreen broad-leaved forests cover the majority of forest areas and have high carbon storage in Xishuangbanna, southwest China. However, stem radial growth dynamics and their correlations with climate factors have never been analyzed in this forest type. By combining bi-weekly microcoring and high-resolution dendrometer measurements, we monitored xylogenesis and stem radius variations of the deciduous species Betula alnoides Buch.-Ham. ex D. Don and the evergreen species Schima wallichii (DC.) Korth. We analyzed the relationships between weekly climate variables prior to sampling and the enlarging zone width or wall-thickening zone width, as well as weekly radial increments and climate factors during two consecutive years (2020 to 2021) showing contrasting hydrothermal conditions in the pre-monsoon season. In the year 2020, which was characterized by a warmer and drier pre-monsoon season, the onset of xylogenesis and radial increments of B. alnoides and S. wallichii were delayed by three months and one month, respectively, compared with the year 2021. In 2020, xylem formation and radial increments were significantly reduced for B. alnoides, but not for S. wallichii. The thickness of enlarging zone and wall-thickening zone in S. wallichii were positively correlated with relative humidity, and minimum and mean air temperature, but were negatively correlated with vapor pressure deficit during 2020 to 2021. The radial increments of both species showed significant positive correlations with precipitation and relative humidity, and negative correlations with vapor pressure deficit and maximum air temperature during two years. Our findings reveal that drier pre-monsoon conditions strongly delay growth initiation and reduce stem radial growth, providing deep insights to understand tree growth and carbon sequestration potential in tropical forests under a predicted increase in frequent drought events.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Betula alnoides; climate response; dendrometer; Schima wallichii; tropical montane forest; wood formation